CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If one of the zeroes of the quadratic polynomial $$(k-1)x^{2}+kx+1$$ is $$-3$$, then the value of $$k$$ is.


A
43
loader
B
43
loader
C
23
loader
D
23
loader

Solution

The correct option is A $$\dfrac{4}{3}$$
Given $$-3$$ is the zero of the polynomial $$(k-1)x^2+ k x+1$$
So $$-3$$ must satisfy the equation $$(k-1)x^2+k x+1=0$$
$$\implies (k-1)(-3)^2+k(-3)+1=0$$
$$\implies 9(k-1)-3 k+1=0$$
$$\implies 9 k-9-3 k+1=0$$
$$\implies 6 k=8$$
$$\implies k=\dfrac{4}{3}$$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image